Shared Single Display Application: An Interactive Patterns Approach - Cheah, Wai Shiang; Edwin, Mit; Alfian, Abdul Halin (SERSC, 2015)
Interactive patterns are able to promote the notion of interaction in groupware application development. Hence, these patterns improve the students’ engagement and promote problem solving collectively. This paper reports on the usability of the interactive patterns in designing and developing a collaborative language application. With interactive patterns, we are able to design and develop two different interactive shared single display education applications. RimbaIlmu is an after school programme to allow students to learn Bahasa Malaysia during their free time. RICLAT is an authoring tool for collaborative presentations. The patterns are useful to enrich the interaction among both education applications. Also, it facilitates more effective communication among the group members and enriches the interaction for students based on the qualitative analysis.